Urinary tract infection: etiology, sensitivity patterns and antimicrobial resistance at a pediatric hospital (Research, Society and Development, 2020)
This study was developed with the objective to identify the bacterial agents of the urinary tract infection, in the pediatric age group, in a Children´s Hospital of Serra Catarinense, distinguish the incidence of urinary tract infection and specify the etiological agent according to age and sex and analyze the profile of sensitivity and resistance. Methodologically, it is characterized by retrospective and cross-sectional study, through consult in the Hospital's database using the procedure code: “treatment of other diseases of the urinary tract” of patients admitted in 2018, selected 52 patients. The following were evaluated: microbial etiology; sensitivity and resistance to antibiotics. As results was twenty-four positive urocultures, twenty female and four male. The most frequent uropathogen was Escherichia coli (70.8%), and its resistance profile was shown to be high for five antimicrobials. It was observed compatibility of research data and literature in relation to sex; and disagreements regarding sex/etiologic agent and age group. There is a higher prevalence of Proteus in females; and greater number of cases in the age group of infants in the study, disagreeing with the literature. Regarding the sensitivity and resistance profile of parenteral antimicrobials, ceftriaxone is in accordance with the literature. The research points to greater resistance regarding the oral use of amoxicillin with clavulanate, SMT-TMP and nitrofurantoin, differing from the literature.